Strategi Perbaikan Makanan Khas Bogor - Ervina Mela; Gunawan Wijonarko; Imas Arti Suciani (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2021)
Bogor constitute one of the tourist destination city in Indonesia, meanwhile, one of the attractions of this city is the indigenous food. However, only a few foods are widely known, therefore, it is necessary to identify the types of Bogor indigenous foods and strategies to improve these foods which are very unpopular to avoid extinction. This study aims to identify Bogor indigenous foods, level of popularity as well as improvement strategy. The methods used include survey, experts interview, and questionnaires while data analysis was performed using Importance Performance Analysis (IPA). Moreover, the results showed that there were 12 Bogor indigenous foods namely, Soto Mie, Soto Kuning, Laksa, Asinan, Doclang, Cungkring, Es Pala, Lapis Talas, Talas Kukus, Roti Unyil, Makaroni Panggang, and Tauge Goreng while the food with the lowest popularity level (very unpopular) is Cungkring. After analyzing the level of satisfaction and importance with IPA, there are 4 attributes of Cungkring that needs to be improved. Improvement strategies include improving spice color, gravel color, packaging and serving speed.